Les compétences transversales, une nouvelle « clé » pour l'insertion ? Enjeux et effets pour les acteurs - Frédérique Bros; Marie-Christine Vermelle; Ioana Boancă (Nantes Université, 2019)
The object of this contribution is to report on how the stakeholders involved in employment access programmes - professionals and young adults - take possession of and give meaning to the concept of transferable skills. After defining the aim of this paper, by presenting the research (Ludo Ergo Sum) and its object i.e. the sociotechnical videogaming training programme (Skillpass) experimented in different social and professional integration programmes in the Hauts-de-France region, the authors develop the design's main impacts identified on the support practices implemented, the practitioners' representations, and their educational and professional uses of this notion. The authors then focus on the view taken on transferable skills by poorly qualified/educated young adults, whom the training programme addresses: what meaning do they give to the work accomplished? What benefits do they gain in terms of reflexivity and integration? All the elements presented in this paper, resulting from the enquiry carried out as part of this research, aim at shedding light on how the stakeholders take possession of, resist or make the best of the requirement for transferable skills, prerequisites to employment access.